Barriers and enablers of local adaptive measures: a case study of Bengaluru's informal settlement dwellers. Issue 3 (4th March 2019) - Deshpande, Tanvi; Michael, Kavya; Bhaskara, Karthik
ABSTRACT: Cities, with their increasing populations, are host to a range of issues including non-climatic factors due to the prevailing development paradigm, discriminatory urbanisation patterns, and weak governance structures. Climate change poses an additional challenge and exacerbates existing vulnerabilities affecting cities and its people, especially the urban poor. This paper highlights the barriers and enablers to climate change-related adaptation experienced in some of Bengaluru's informal settlements. The barriers described in the paper include economic, social, governance and information related issues that impede local actions and increase vulnerabilities. Enabling factors such as improving social and human capital, gaining formal recognition and most importantly support from agencies (e.g. local government, civil societies, and community leaders), help overcome some of the barriers or challenges. Hence, local level adaptation measures mainstreamed with local developmental agendas help address some of the structural causes of vulnerability. Contextual policies and interventions can facilitate successful local level adaptation measures.